Firefly algorithm based multivariable PID controller design for MIMO process - Ramyashree, J; R. Roja, M; Sivagurunathan, G; Kotteeswaran, R (International Journal of Engineering and Technology, 2018)
Distillation is the process of separating the components or substances from a liquid mixture by selective boiling and condensation. It is one of the most underestimated fields of chemical engineering and has been around for well over hundred years. This paper deals with the tuning of centralized and decentralized Multivariable PID controller for Wood and Berry distillation column using Firefly algorithm (FA). FA uses controller parameters as decision variables and minimization of IAE as objective function. At the end of the search, optimum solutions for controller parameters are obtained which upon implementation provides challenging results for both top and bottom products. Simulation has been carried out using Matlab/Simulink platform.